Notes on the Coptic translations of the construction en tō + infinitive in Luke - Alcock, Anthony (2010)
This note is about a grammatical structure that occurs in the Gospel of Luke much more frequently than in any of the other gospels: the prep. έν followed by the substantivized infinitive. The two major dialects of Coptic (Sahidic and Bohairic) have a similar construction, but it is by no means used consistently to translate the Greek construction. A brief discussion of similar constructions in earlier phases of Egyptian is followed by the text of the Sahidic and Bohairic translations of the Luke passages, with brief comments.
Diese Notiz behandelt eine grammatische Struktur, die im Lukasevangelium viel häufiger vorkommt als in den anderen Evangelien: die Präp. έν mit dem substantivierten Infinitiv. Die beiden Hauptdialekte der koptischen Sprache (Sahidisch und Bohairisch) haben eine ähnliche Struktur, die allerdings nicht konsequent verwendet wird, um die griechische Konstruktion zu übersetzen. Nach einer kurzen Diskussion ähnlicher Konstruktionen in der früheren Phase der ägyptischen Sprache werden die koptischen Übersetzungen der Lukasstellen aufgezählt, mit einem kurzen Kommentar.
Keywords: Bibel; Griechisch; Koptisch